The fabric of an industry has evolved with technology. - Joch, Alan (Architectural Record, 2003)
It's tempting to think of soft materials like carpets, textiles, and coverings as mere decorations or backdrops for the indoor spaces they occupy. But interior architects choose these materials with great care, knowing they convey as much of a design aesthetic as the layout and lines of the enclosing space itself. As they have done with building construction, innovations in digital design techniques and manufacturing methods have changed the way these products are made. Designers within mills and independent textile artists alike are using a combination of technologies to make their ideas into reality. The tools they use include design software, scanners, and image editing applications.